PENYULUHAN TENTANG KEPEMIMPINAN DALAM UNIT REKAM MEDIS RSU SEMBIRING - Hengky Frengki Manulang; Jon Piter Sinaga (INSTITUT KESEHATAN DELI HUSADA, 2021)
In an organization of urgency on the capability and capacity of a leader really needed an effort to run and maintain the organization to an organization that still walk and run functions as where it should be so reasonable that a leader in case this should continue to improve capacity as a leader. Community service activities in the form of This extension is a response to problems of capacity of a leader in managing the organization that he leads are often times encountered was the lack of capacity of a leader who in the end will result in less well-organized organization and ultimately led walk not the function of each part of an organization. This activity generally aims to provide knowledge in order to increase the capacity of the leadership element in managing the hospital medical record unit , and for the material in this out reach activity itself is material that is processed by the team based on the model of leadership theories . This activity was held at Sembiring hospital, Deli Tua Subdistrict . Overall, this activity ran smoothly starting from the preparation and planning stage, the implementation stage, until the report writing stage went smoothly without any significant obstacles. The enthusiasm of the participants extension consisting of the ranks of the sick as well as the leadership of the unit, especially medical records show that the activities of counseling is responded to well by the participants. Response positive that shown by these participants indicated that this activity brings impacts that are positive for the leadership of medical records , especially in the increase the understanding of the ranks of the hospital in order creation work order management that is optimal.